Comparison of Shockwave Lithotripsy and Laser Ureterolithotripsy for Ureteral Stones - Tuncer Bahçeci; Fuat Kızılay; Ahmet Çağ Çal; Adnan Şimşir (Journal of Urological Surgery, 2021)

(untitled)
Objective:This study aimed to compare shockwave lithotripsy (SWL) with ureteroscopic lithotripsy (URS) for ureteral stones in terms of stone-free rates, complication rates, and overall treatment costs.Materials and Methods:Data of 886 adult patients who underwent URS or SWL were retrospectively evaluated, of which 184 patients underwent SWL and 702 underwent URS. The groups were compared in terms of patient characteristics, stone-free rates, complications, and costs.Results:No significant differences were found between the groups in terms of age, gender, and relevant sides (p>0.05). A significant difference was observed in favor of SWL for upper ureteral stones <10 mm regarding treatment success (p=0.018), and no significant difference was observed between the two groups in terms of mid- and distal ureteral stones (p=1 and p=0.655, respectively). Complications were classified according to the modified Clavien-Dindo grading system. No major complications were observed in the two groups, except for one patient with Clavien-Dindo grade IVa complication. SWL was significantly more economical than URS (p<0.001).Conclusion:The results of this study suggest that SWL can be recommended as the primary treatment option for upper ureteral stones <10 mm because of its high stone-free rates and low overall costs.